2015
DOI: 10.1615/intjmedmushrooms.v17.i1.40
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Composition and Bioactive Constituents of Artificial Culture of Ophiocordyceps longissima (Ascomycetes)

Abstract: In this study, the compositions of Ophiocordyceps longissima mycelia, synnemata, and fruiting bodies were first analyzed in order to clarify its chemical basis for development as a health food or medicine. We found that the contents of crude protein, polysaccharides, and macroelements were highest in mycelia, whereas effective components, including mannitol, ergosterol, adenosine, inosine, Zn, and Se, were lowest in mycelia. Polysaccharide, mannitol, and ergosterol levels in synnemata (2.33, 4.54, and 0.66 g/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, in other contexts, TGF-β can also activate NF-κB, contributing to processes like fibrosis observed in CKD [ 58 ]. Polyphenols like curcumin [ 57 ], epigallocatechin-3-gallate (EGCG) [ 58 ], resveratrol [ 59 ], a synthetic caffeamide derivative [ 60 ], and lignophenol [ 61 ] are believed to exert their beneficial effects by modulating these pathways, as seen for polyphenol-rich foods and drinks, such as dark chocolate [ 62 , 63 ], Clitoria ternatea flower petal extract [ 64 , 65 ], açaí [ 66 , 67 ], mushrooms [ 68 , 69 ], corn silk [ 70 ], sorghum [ 71 ], probiotic drinks [ 72 ], and unfermented grape juice [ 73 ]. They can activate Nrf2, promoting the antioxidant defense system, and/or inhibit NF-κB, TGF-β, and/or TNF-α, thereby reducing inflammation and the associated oxidative stress in CKD patients [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in other contexts, TGF-β can also activate NF-κB, contributing to processes like fibrosis observed in CKD [ 58 ]. Polyphenols like curcumin [ 57 ], epigallocatechin-3-gallate (EGCG) [ 58 ], resveratrol [ 59 ], a synthetic caffeamide derivative [ 60 ], and lignophenol [ 61 ] are believed to exert their beneficial effects by modulating these pathways, as seen for polyphenol-rich foods and drinks, such as dark chocolate [ 62 , 63 ], Clitoria ternatea flower petal extract [ 64 , 65 ], açaí [ 66 , 67 ], mushrooms [ 68 , 69 ], corn silk [ 70 ], sorghum [ 71 ], probiotic drinks [ 72 ], and unfermented grape juice [ 73 ]. They can activate Nrf2, promoting the antioxidant defense system, and/or inhibit NF-κB, TGF-β, and/or TNF-α, thereby reducing inflammation and the associated oxidative stress in CKD patients [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…1-octene-3-alcohl and butylated hydroxytoluene [69] ↓ BUN and Scr ↓ content of ROS in renal tissues ↓ oxidative stress ↑ SOD and GSH-PX [68] Gallic acid, catechin and derivatives, and rutin and derivatives [70] ↓ blood urea nitrogen and serum creatinine [70] Luteolinidin and 5-methoxyluteolinidine [71] ↓ oxidative stress ↑ serum SOD and TAC ↓ serum MDA decreased [71] Hydroxycinnamic acids and flavonoids and caffeic acid derivatives [110] ↑ SOD 1 activity ↓ IL-1β, TNF-α, and IL-6 production [72] Hydroxybenzoic and hydroxycinnamic acids, stilbenes [54] ↓ LDLs and cholesterol ↓ oxidative DNA damage [73] Curcumin [79] ↓ serum urea and creatinine ↓ HO1 and INOS mRNA expression ↑ GSH concentration, GR, CAT, and SOD activities ↓ LPO and DNA fragmentation [79] Ellagitannin geraniin [80] ↓ relative weights of pancreas, liver, heart, and aorta ↓ plasma glucose ↓ TG, non-HDLs and total cholesterols, ALT, AST, CK, and Cr [80] Protocatechuic acid [81] ↓ BMI ↓ SOD activity in liver and muscle homogenates ↑ GSH activity in muscle ↓ MCP-1, IL-1b, CRP [81] 3,4-dihydroxybenzoic acid [82] ↓ TNF-α expression by 0.12 times [82] Ferulic and benzoic acid derivatives, quercetin derivatives, flavonone glycosides [83] ↓ cholesterol, LDLs, and plasma TGCs [83] 7-O-Galloyl-d-Sedoheptulose [84] ↓ serum levels of triglycerides, total cholesterol, LDL/VLDL-cholesterol, NEFAs, and TBA-reactive substances ↓ serum levels of ALT, AST, creatinine, and urea nitrogen [84] Thymol [85] ↓ urinary glucose, urinary urea, and urinary protein ↓ TBARS and LOOH ↑ SOD, catalase, GPx, GST, and GR ↓ SREBP-1c, TGF-b, and VEGF proteins [85] Protocatechuic acid [89] ↓ insulin Improved AGE expression and histological changes in both glomerular hypertrophy and interstitial crushing [86] Protocatechuic acid, gallic acid, catechin, gallocatechin, and rutin [87] ↓ triacylglycerol and total cholesterol levels ↓ BUN, blood creatinine, and blood pressure ↓ ratio of urine albumin/urine creatinine Ameliorated mesangial fibrosis in part via the Ras/PI3K/Akt signaling pathway.…”
Section: Compound Reported Bioactivitymentioning
confidence: 99%
“…We previously reported that the ethyl acetate extract of Cordyceps cicadae fermented broth had a significant inhibitory effect on Candida albicans , which was selected as the best indicator of the antibacterial activity and the antifungal compound isolated from the fermentation broth of C. cicadae was myriocin (Hu et al 2016). The myriocin in RCEF3666, RCEF3890 and RCEF3891, 3 strains of Ophiocordyceps longissima , and 1 strain of Isaria cicadae RCEF6212 and its mycelia was also identified, and the results showed that only RCEF3891 ( O. longissima ) contained myriocin (Zhang 2014). Then the artificial cultures of a large number of Isaria cicadae strains deposited at the laboratory were detected, and myriocin were still not detected.…”
Section: Discussionmentioning
confidence: 99%